The influence of functional asymmetry of motor and sensor systems on the development of figurative and verbal logical thinking among children of junior and middle school age - Rodzinskа Tetyana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article highlights the relevance of this issue and presents the results of a pilot study aimed at indicating whether there is a relationship between functional asymmetry and the level of development of imaginative and verbal-logical thinking. For more than 150 years, psychologists have studied the impact of functional asymmetry on human development. Depending on this, there are mainly groups: right-handed (right-handed), left-handed (shulg), ambidexter. However, in the scientific community, the connection between the left and right hemispheres is quite deep and not clear. For the sake of clarity of results, this study was conducted on a sample of children in grades 4-6. The research was carried out with the help of a diagnostic complex, which includes psychodiagnostic methodology for determining the integral index of figurative and verbal-logical thinking, as well as diagnostics of functional asymmetry of motor and sensory systems. The relationship between this study and the results of our pilot study is being traced. In addition, the study presents data from different social strata. For example, among the lyceum students the "mosaic" asymmetries were more common, while the pure "right-handed" type was often noticed among the students. This pilot study is the basis that defines a new space for research, namely the study of thinking and detailed analysis depending on two groups of variables – asymmetries: hand, foot, ear, eye; and classic units of analysis – age, gender, social status, nationality. The data obtained indicate a tendency for such an impact. In the course of the study, no significant influence of the dominance of sensory and motor systems on the level of development of figurative and verbal-logical thinking in young and middle school children (grades 4–6) was found. Trends in the influence of the dominance of the visual sensory system on the development of imaginative thinking have been identified, as well as a tendency to float on the development of thinking on the side of the motor system, in particular the leading leg. There is a recommendation to repeat the study on a larger sample.